MODEL PENYELESAIAN SECARA ALTERNATIF DALAM PERADILAN PIDANA (STUDI KHUSUS TERHADAP MODEL PENYELESAIAN PERKARA PIDANA OLEH LEMBAGA KEPOLISIAN) - Sudaryono Sudaryono; Muhammad Iksan; Kuswardani Kuswardani (Jurnal Penelitian Humaniora, 2012)
The problem statements of this study include: 1) what are the types of criminal cases handled by the police; 2) how do the police handle the cases; and 3); how do the police’s insight of handling them alternatively. In the first year, the study aims to 1) establish the types of criminal cases handled by the police; 2) inventory the ways the police handle them; and (3) describe the police’s insight of a model for handling those alternatively. Hopefully, it can be beneficial for academicians and policy makers. For the academicians, it can be meaningful to contribute to criminal law development, particularly an alternative model for handling criminal cases. For the policy makers, it can be useful to develop a conceptual thinking to make a policy of handling criminal cases oriented to substantive justice.The study is a research of sociological law with qualitative approach. For this, the data included primary and secondary. The data employed a content analysis with legal and theoretical interpretations.Reserch product: In running its juridical responsibility, from January to May, 2011 the Polresta Surakarta has handled a variety of criminal cases. The types of these cases handled by the Polresta in 2011, particularly for five months, consisted of 33 cases. Out of the 2 felony cases were conventional at 25 criminal cases and unconventional (transnational) at 8 criminal cases. In handling the criminal cases, the Polresta Surakarta uses a fixed procedure as a reference to them, as stipulated in the Act of the Criminal Code, operating rule and guidance and technique of the Indonesian Police Administration. In facing the implication of the ADR to handle criminal cases, the Police have actually taken a better action. In the Telegram of the Criminal Investigation Bureau (STR), the Sub-Division of the STR of the Indonesian Police No ST/110/V/2011, dated on May 18, 2001 on the Implication Guidance of the ADR in the Rank of the STR of the Indonesian Police, the STR of the Indonesia Police will apply the ADR to handle criminal cases. Unfortunately, the policy is delayed with the Telegram of the STR of the Indonesian Police No ST/209/IX/2011, dated September 6, 2001 on Delaying the Implication of the ADR in the Rank of the STR of the Indonesian Police.